2019
DOI: 10.1038/s41598-019-46910-5
|View full text |Cite
|
Sign up to set email alerts
|

Sonication accelerated formation of Mg-Al-phosphate layered double hydroxide via sol-gel prepared mixed metal oxides

Abstract: Single-phase magnesium-aluminium layered double hydroxide (LDH) intercalated with dihydrogen phosphate was successfully produced by hydration of nanopowder of the respective mixed metal oxide (MMO) obtained using sol-gel based method followed by a two-step anion exchange hydroxide-to-chloride and chloride-to-phosphate. The MMO with the metal cation ratio of Mg/Al = 2:1 was prepared using the aqueous sol-gel method. Processes of the parent Mg 2 Al-OH LDH formation and the successive anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The XRD of chitosan exhibited the semi-crystalline nature of chitosan with two distinct peaks at 2θ = 10° and 50° due to (020) and (110), respectively. The XRD of LDH-INS-CSNPs showed a diffraction peak shifting of (003) and (006) specifying the synergy between chitosan and LDH [28]. Besides, the disappearance of the small diffracted peaks of LDH may refer to one of the following reasons: removal of water molecules, rearrangement of Zn/Al ions, and / or adsorption of insulin molecules on the surface of LDH.…”
Section: Structure and Characterizationmentioning
confidence: 98%
“…The XRD of chitosan exhibited the semi-crystalline nature of chitosan with two distinct peaks at 2θ = 10° and 50° due to (020) and (110), respectively. The XRD of LDH-INS-CSNPs showed a diffraction peak shifting of (003) and (006) specifying the synergy between chitosan and LDH [28]. Besides, the disappearance of the small diffracted peaks of LDH may refer to one of the following reasons: removal of water molecules, rearrangement of Zn/Al ions, and / or adsorption of insulin molecules on the surface of LDH.…”
Section: Structure and Characterizationmentioning
confidence: 98%
“…Obtained LDH were Mg(2)Al-OH and Mg(2)Al-10%Ce-OH. It was recently shown that direct hydroxide-to-phosphate anion exchange is unlikely but can be implemented via formation of the intermediate chlorine-intercalated phase [14].…”
Section: Anion Exchange and Formation Of Chlorine-and Phosphate-intercalated Ldhmentioning
confidence: 99%
“…1 g of the Mg(2)Al-Cl powder was immersed in the solution followed by addition of NaH 2 PO 4 to adjust the pH value to 7.5. At such conditions, the intercalated anion is dihydrogen phosphate, H 2 PO 4 - [14]. The reaction was sonication-assisted and took 8 min.…”
Section: Anion Exchange and Formation Of Chlorine-and Phosphate-intercalated Ldhmentioning
confidence: 99%
See 1 more Smart Citation
“…The general formula of an LDH is expressed as [M M (OH) ] (X ) / ⋅ mH O where M and M are divalent and trivalent metal cations, respectively, stands for the molar ratio M /(M + M ) and X represents an anion having charge [35]. Usually, the divalent and trivalent metal cations are Mg , Zn , Cu , Mn , Co , Al , Cr and Fe ions but also lanthanides and bismuth, having comparable ionic radii, can isomorphically substitute the trivalent metallic cations [36]. For what concern the inter-domain anions, F , Cl Br , I , oxides as NO , CO , sulfates and chromates or more complex organic and inorganic compounds can be present as counterbalancing species.…”
Section: Introductionmentioning
confidence: 99%